EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN ISPA PEDIATRI DI INSTALASI RAWAT INAP PADA SALAH SATU RUMAH SAKIT KOTA TEGAL PERIODE 2024 - Apriliani, Amanda Afni (Journal Pharmactive, 2025)
Acute Respiratory Infections (ARI) are among the most common infectious diseases in pediatric patients and remain a major cause of morbidity and mortality worldwide. The increase in ARI cases is directly associated with the high use of antibiotics, which can contribute to bacterial resistance if not aligned with proper therapeutic guidelines. Therefore, this study aimed to evaluate the pattern and rationality of antibiotic use in pediatric patients with ARI in the hospital's inpatient ward in Tegal City during the 2024 period. This study employed an observational method with a retrospective approach. The evaluation of antibiotic use was conducted using the Gyssens method to determine the appropriateness of use based on rationality categories. The results showed that the most commonly used antibiotics were ceftriaxone (65.5%), cefotaxime (16.2%), and amoxicillin (7.14%). Analysis using the Gyssens method indicated that in 74.02% of cases, more effective antibiotics were available; in 1.94% of cases, more affordable options could have been used; in 18.8% of cases, antibiotics were used for too short a duration; and in 3.24% of cases, incorrect dosages were prescribed. Only 1.94% of cases involved rational antibiotic use. In conclusion, based on the Gyssens method, 98.05% of antibiotic use in this study was considered irrational, while only 1.94% was deemed rational.